Supporting Sustainable Development Goal 4 Through Scientific Argumentation: A Mixed-Methods Study of High School Students' Argumentation Skills on Acid–Base Concepts - Shella Befi Wahyuning; Muhammad Haris Effendi; Wilda Syahri; Kriswantoro (Postgraduate, University of Mataram, 2026)
Scientific argumentation is an essential competency in 21st-century science education because it enables students to construct claims supported by evidence and scientific reasoning. This study aimed to analyze the scientific argumentation skills of senior high school students on acid–base concepts and identify the factors influencing these skills. A mixed-methods approach with a sequential explanatory design was employed involving 216 Grade XI students from SMA Negeri 1 and SMA Negeri 5 Jambi City, Indonesia. Quantitative data were collected using an essay test based on Toulmin's Argumentation Pattern (TAP), while qualitative data were obtained through classroom observations, questionnaires, and interviews with teachers and students. Quantitative data were analyzed using descriptive statistics, one-way ANOVA, and Tukey HSD tests, whereas qualitative data were analyzed using the Miles and Huberman interactive model. The findings revealed significant differences in students' argumentation skills among the six classes (F = 21.63, p < 0.001). Students from SMA Negeri 1 generally demonstrated higher levels of argumentation, predominantly at Levels 4 and 5 of the Toulmin framework, whereas students from SMA Negeri 5 were distributed across Levels 1 to 5, indicating greater variation in argumentation quality. The qualitative findings showed that conceptual understanding, active participation in classroom discussions, critical thinking skills, and a learning environment that encourages scientific dialogue were the primary factors influencing students' argumentation skills. These findings highlight the importance of integrating learning activities that explicitly foster claim–evidence–reasoning construction to strengthen students' scientific argumentation and support quality science education.